Acquired Phototrophy and Its Implications for Bloom Dynamics of the Teleaulax-Mesodinium-Dinophysis-Complex - Anschütz, Anna-A.; Flynn, Kevin J.; Mitra, Aditee (Frontiers in Marine Science, 2022)
The dinoflagellate Dinophysis is responsible for causing diarrhetic shellfish poisoning impacting shellfish aquaculture globally. Dinophysis species are invariably plastidic specialist non-constitutive mixoplankton (pSNCM), combining phagotrophy with acquired phototrophy. Dinophysis acquires phototrophy from another pSNCM, the ciliate Mesodinium, which in turn acquires phototrophy from cryptophytes within the Teleaulax-Plagioselmis-Geminigera clade. Despite this trophic linkage, the temporal dynamics of cryptophyte-Mesodinium-Dinophysis remain poorly understood. In this study, we present the first Teleaulax-Mesodinium-Dinophysis (TMD)-complex system dynamics model. Using this, we explored the dynamics of TMD interactions under different ecological settings. Temperature, nutrient load, mixed layer depth, and irradiance all greatly influenced the timing and magnitude of the TMD-complex interactions and, as a result, Dinophysis bloom duration and peak. Availability of Mesodinium and temporal matching of its growth to that of Dinophysis are also key biotic factors; the timing of Mesodinium availability impacts the potential of Dinophysis growth for up to 3 months. Integrating our TMD-complex model with a suitable hydrodynamic model could greatly improve our understanding of bloom formation and aid in forecasting harmful algal bloom (HAB) events. Future monitoring of Dinophysis would also be enhanced by the monitoring of the precursor prey species, Teleaulax and Mesodinium, which are rarely accorded the same effort as the HAB forming dinoflagellate.